Aspectos cognitivos na doença de parkinson e sua relação com o polimorfismo val158met da catecol-O-metiltransferase - Lima, Daiane Borba de (2012)
Although Parkinson s Disease (PD) is predominantly a movement disorder, the presence of cognitive problems related to frontal function, even in the earliest stages has been observed. These problems include attentional, executive and memory deficits. A study using an experimental paradigm developed to investigate the effects of different encoding instructions on contextual memory showed that, unlike healthy controls, PD patients could not reverse their contextual memory deficits and take any advantage of encoding instructions. However, it is unclear whether they have a memory deficit or executive dysfunction would be accountable for results. Attentional and executive deficits observed in PD patients have important implications for daily activities, mainly when patient perform concomitant cognitive and motor activities that are attention demanding. Catechol- O-methyltransferase (COMT) is an enzyme that degrades cortical dopamine. Some studies have examined the relationship between the COMT val158met polymorphism and executive function in PD patients and have found low enzyme activity, associated to met/met polymorphism- implying higher prefrontal dopamine levels- is related to worse performance. However, a recent study did not demonstrate a direct effect of COMT genotype on the executive performance. The present study aimed to characterize different cognitive parameters of patients with PD and to assess their relationship with the COMT polymorphism. In this study participated 18 patients with early disease stage PD and 18 healthy adults matched for age, gender and education. Patients were selected from a data bank of patients genotyped for COMT polymorphism. All participants completed the Wisconsin Card Sorting Test (WCST), the Stroop Color and Word Test, and dual tasking paradigm. In addition, patients completed a contextual memory paradigm. No effect of COMT val158met genotype on frontal function in patients with PD (executive function and contextual memory) was observed. A decrease in cognitive task performance under dual-tasking was observed in PD patients, by contrast to healthy controls. Relative dual-task cognitive cost was significantly greater for PD patients compared to controls in the arithmetic-walking condition. In conclusion, difficulties in performing a cognitive task while walking can be influenced by the executive/attentional load of the task.